The Role of Vaginal Mesh Procedures in Pelvic Organ Prolapse Surgery in View of Complication Risk - David R. Ellington; Holly E. Richter (Hindawi Limited, 2013)
Synthetic transvaginal mesh has been employed in the treatment of pelvic organ prolapse for more than a decade. As the use of these devices increased during this period so did adverse event reporting. In 2008, the Food and Drug Administration (FDA) Public Health Notification informed physicians and patients of rising concerns with the use of synthetic transvaginal mesh. Shortly thereafter and in parallel to marked increases in adverse event reporting within the Manufacturer and User Device Experience (MAUDE), the FDA released a Safety Communication regarding urogynecologic surgical mesh use. Following this report and in the wake of increased medical industry product withdrawal, growing medicolegal concerns, patient safety, and clinical practice controversy, many gynecologists and pelvic reconstructive surgeons are left with limited long-term data, clinical guidance, and growing uncertainty regarding the role of synthetic transvaginal mesh use in pelvic organ prolapse. This paper reviews the reported complications of synthetic transvaginal mesh with an evidence-based approach as well as providing suggested guidance for the future role of its use amidst the controversy.